Developing a Methodology to Evaluate Enterprise Education Programmes - Athayde, Rosemary; Hart, Mark (Senate Hall, 2012)
The contribution of this research to existing entrepreneurship theory is to present a conceptual model for understanding enterprise potential in young people in an educational context, and to demonstrate how enterprise potential can be measured. The overall aim of this research was to develop an evaluation tool which can be used in future evaluation studies of enterprise education. The tool can be used to overcome some of the limitations of evaluation studies, which have been identified by researchers. Longitudinal studies using the tool will enable consistent comparison of entrepreneurial attitudes, and it is recommended that it is used in conjunction with objective measures of entrepreneurial behaviour such as actual start-up activity. Enterprise potential was conceptualised as high entrepreneurial self-efficacy which was operationalised as positive attitudes towards five dimensions: leadership, achievement, personal control, creativity and intuition. Based on this conceptual framework the attitudes to enterprise (ATE) test was developed. This new measure provides a tool to evaluate enterprise programmes, enabling researchers to take into account other moderating factors, which may influence attitudes towards enterprise such as gender, type of school, ethnic background, and a family background of business ownership. For policy makers the tool can provide evidence of the efficacy of different types of enterprise education programmes for different target groups, thus helping to identify how best to target resources and investment. A series of validity and reliability tests was used to develop and refine the ATE test including: factor analysis; Cronbach alpha tests; discriminant and nomological validity tests; and a test for criterion validity using a second independent sample. Limitations to this testing indicate a need for further tests particularly criterion validity tests, using new, larger and more diverse samples
Keywords: entrepreneurship education evaluation